Subnational border reforms and economic development in Africa - Thushyanthan Baskaran; Sebastian Blesse (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
Arbitrarily designed borders have been identified by a recent literature as an important reason why sub-Saharan Africa remains one of the poorest regions on the globe. Accordingly, border changes may be a way to promote growth on the African continent. In this paper, we study the effect of subnational border reforms on local economic development (proxied by nighttime luminosity) by tracking provincial-level border changes in Africa during 1992-2013 with GIS techniques. Difference-in-difference regressions suggest that mergers have strong positive effects on economic development. Splits, too, have positive effects, but they are substantially smaller on average. To understand why the economic impact of splits and mergers differs in magnitude, we investigate transmission channels. We link border changes to geocoded conflict data and survey evidence on political attitudes. We find that the differences between splits and mergers are possibly due to different underlying motives for these two types of border reforms. Splits seem to affect development through higher political stability, i.e. a lower incidence of conflicts and more benign political attitudes of citizens, while mergers presumably work through an improvement in administrative efficiency.
Keywords: D73; H77; R11; 330; Border changes; economic development; night-light data; Africa